Utilização de Método Indireto para Predição da Composição Química Corporal de Zebuínos - Jorge, André Mendes [UNESP]; Fontes, Carlos Augusto De Alencar; Paulino, Mário Fonseca; Júnior, Paulo Gomes (My University, 2000)
The objective of this study was to develop equations to predict chemical body composition from zebu cattle, based on chemical composition from carcass representative section. Sixty-three young bulls from Gyr, Guzera, Nellore and Mocho de Tabapuã breeds were used. Body content of protein, fat and minerals were determined on samples from the carcass section that included the 9th, 10th and 11th rib joint (HH joint), and from the remaining body tissues. Protein, fat, energy and ash contents from the HH joint, except for magnesium, were closely related to protein, fat, energy and ash contents in the body. Prediction equations based on chemical composition from HH joint showed to be reliable for comparative studies of body composition of zebu cattle.
Use of Indirect Method to Predict Chemical Body Composition in Zebu Cattle
Keywords: Body composition; Cattle; Prediction equations